Survey of the therapeutic approach and efficacy of pentosan polysulfate for the prevention and treatment of equine osteoarthritis in veterinary practice in Australia. Issue 12 (December 2014) - Kramer, CM; Tsang, AS; Koenig, T; Jeffcott, LB; Dart, CM; Dart, AJ
<x xml:space="preserve">Abstract</x> Objective To survey veterinary practitioners in Australia on how they administer pentosan polysulfate (PPS) to horses and their perceptions of the efficacy of PPS for: the prevention and treatment of osteoarthritis (OA), the treatment of OA when PPS is combined with other drugs, and the efficacy of PPS compared with other disease‐modifying osteoarthritic drugs. Design Practitioners were contacted by email, which contained a link to an online survey. Results A total of 76 responses (34.5%) to the survey were received. Respondents most commonly used PPS as prophylactic therapy prior to competition (80.3%). As a prophylactic agent, PPS was considered by 48.2% of respondents to have high efficacy. The most common dose regimen for prevention and treatment of OA was 3 mg/kg, intramuscularly, once weekly for 4 weeks followed by monthly injections. Most respondents (78%) combined PPS with other drugs for treatment of OA. Intra‐articular corticosteroids and hyaluronate (HA) was the most common drug combination used with PPS. PPS was preferred as a prophylactic agent when compared with HA (88.7% vs 11.3%). For treating OA, 83% of respondents considered a combination of PPS, HA and glucosamine to be more efficacious than PPS alone. However, the most common reason not to use this combination was cost (79.1%). Conclusion All respondents used PPS for prophylaxis and/or treatment of OA despite limited published scientific evidence proving its efficacy in horses. Further research is necessary to provide evidence of the clinical efficacy of PPS for the prevention and treatment of OA in horses.